A note on Mawlāy ‘Abd al-Qādir b. Muḥammad al-Sanūsī and his relationship with the Caliphate of Ḥamdallāhi - Mohamed Diagayété (Afriques)
This article explores the relationship between the Caliphate of Ḥamdallāhi and Timbuktu. In particular, it focuses on one scholar from Timbuktu whom scholars have neglected so far in the historiography of 19th-century West Africa: Mawlāy ‘Abd al-Qādir al-Sanūsī. The article provides a biography of this scholar, who acted as Timbuktu judge and amīr of the city on behalf of Ḥamdallāhi, and introduces his correspondence with the caliphate’s capital. More generally, this contribution shows the potential of investigating manuscript archives to better understand the intellectual, political, social, and economic history of pre-colonial West Africa. Furthermore, in the appendixes the author presents translations of three letters written by Mawlāy ‘Abd al-Qādir al-Sanūsī.